Copper-resistant microorganisms isolated from Antarctic island Galindez - Matveeva, N.A.; Tashyreva, G.O.; Tashyrev, O.B. (Український антарктичний журнал, 2006)
The copper-resistant microorganisms were isolated from soils of Antarctic island Galindes. It was shown that these microorganisms can grow on the medium with concentration of Cu²⁺ ions 1000–3000 ppm. Изучены микробные ценозы антарктического острова Галиндез и выделены культуры микроорганизмов, которые могут расти на среде с содержанием ионов меди до 1000-3000 мг/л. Досліджено мікробні ценози антарктичного острова Галіндез та виділено культури мікроорганізмів, що ростуть на середовищі зі вмістом іонів міді 1000 -3000 мг/л.